2017
DOI: 10.1039/c6nr10022h
|View full text |Cite
|
Sign up to set email alerts
|

Photonic nanorods with magnetic responsiveness regulated by lattice defects

Abstract: Herein, we use experiments and numerical simulations to demonstrate a novel class of magnetically responsive photonic crystals (MRPCs) based on photonic nanorods which exhibit multiple optical properties in a magnetic field (H) due to their fixed photonic nanorods and H-tunable lattice defects. As an example, superparamagnetic FeO@polyvinyl pyrrolidone (PVP)@SiO photonic nanorods were fabricated through a polyacrylic acid-catalysed hydrolysis-condensation reaction of γ-mercaptopropyltrimethoxysilane around cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…For obtaining magnetic nanoparticles as the main body of the "rod-like" nanomotors ( Figure 1(a)), we used hydrothermal synthesis [68,69] to acquire Fe 3 O 4 nanoparticles with the diameter of about 400 nm (Figure 1(b)). Then, an extra magnetic field of about 0.9~3.5 mT with fixed direction was applied, the magnetic nanoparticles with permanent magnetic dipoles would align themselves according to the external magnetic field, and at the same time, also attract each other to form short chains [70] ( Figure S1). Then, we grow a thin layer of silica on the external surface of the cross-linked chains to "fix" the shape of the short chains and form rigid nanorods (see more details in Materials and Methods and Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%
“…For obtaining magnetic nanoparticles as the main body of the "rod-like" nanomotors ( Figure 1(a)), we used hydrothermal synthesis [68,69] to acquire Fe 3 O 4 nanoparticles with the diameter of about 400 nm (Figure 1(b)). Then, an extra magnetic field of about 0.9~3.5 mT with fixed direction was applied, the magnetic nanoparticles with permanent magnetic dipoles would align themselves according to the external magnetic field, and at the same time, also attract each other to form short chains [70] ( Figure S1). Then, we grow a thin layer of silica on the external surface of the cross-linked chains to "fix" the shape of the short chains and form rigid nanorods (see more details in Materials and Methods and Figure 1(c)).…”
Section: Resultsmentioning
confidence: 99%
“…Stabilization of nanoclusters by means of both PVP and SiO 2 has also been recently developed. Fe 3 O 4 @PVP@SiO 2 photonic nanorods made of nanoclusters have been generated by means of a magnetic field . The nanorods are different in terms of both length (i.e., number of nanoclusters forming the chain) and interparticle distance.…”
Section: Artificial Materialsmentioning
confidence: 99%
“…In this regard, similar to the traditional self-assembling methods, MRPCs are required to be prepared in suitable particle sizes for visible spectral segments and narrow particle size distribution. Accordingly, recent studies have found that surface-active agents, such as polyacrylic acid (PAA) (Ge et al, 2007) (Figures 1A,B), polyvinylpyrrolidone (PVP) (Ma et al, 2017) (Figures 1C,D) and oleic acid (OA) (You et al, 2017) (Figures 1E,F) were usually coated on MNPs or a carbon nanolayer with a large number of carboxyl groups (Wang et al, 2010) (Figures 1G,H) so as to introduce a large amount of charge on the MNPs surface with a large amount of charge to balance the attraction between MNPs so that it could disperse evenly in the solvent. Basically, in the absence of EMF, these synthesized SMNs are randomly dispersed and scattered distribution in an aqueous solution which is known as Brownian motion.…”
Section: Basic Principles Of Mrpcsmentioning
confidence: 99%